Dimensions of learning : - Marzano, Robert J. (Mid-continent Research for Education and Learning, 1997)
Dimensions of Learning is an extension of the comprehensive research-based framework on cognition and learning described in Dimensions of Thinking: A Framework for Curriculum and Instruction (Marzano et al., 1988), published by the Association for Supervision and Curriculum Development (ASCD). Dimensions of Learning translates the research and theory explained in Dimensions of Thinking into a practical framework that K-12 teachers can use to improve the quality of teaching and learning in any content area. The Dimensions of Learning Research and Development nsortium, which worked on the model for two years, was made up of more than ninety educators, including the author team from the first edition of this manual.